Republic of Moldova : Technical Assistance Report-Government Finance Statistics Mission (October 2-8, 2019). (IMF Staff Country Reports; Country Report, 2020)
In response to a request from the European Department, a Public-Sector Debt Statistics (PSDS) technical assistance (TA) mission was conducted in Chisinau during October 2-8, 2019. The mission funded by the Data for Decisions (D4D) multi-donor trust fund and followed up on a D4D Public Sector Debt Statistics (PSDS) workshop held in Vienna, Austria during July 2019, where participants from Moldova identified data gaps with current compilation of debt statistics. The mission primarily worked with the Ministry of Finance (MOF) Public Debt Department (PDD), but also had discussions with the Budget and Treasury Department. Outside the MOF, the mission had meetings with the Public Property Agency (PPA), the Municipality of Chisinau and the National Bank of Moldova (NBM). Finally, the mission also held a joint meeting with representatives of a separate IMF TA Mission on sectoral accounts with Treasury and attended the concluding meeting of that mission with the NBM.